Szoboravatás - Nyirkos István mellszobrának avatása - Bitskey, István (Gerundium, 2017)
The Inauguration of the Bust of István Nyirkos. A memorable educator of recent decades has been the well-liked and popular Professor of Linguistics István Nyirkos (1933–2013), whose memory is enhanced by a statue erected on the sports ground of the Athletic Club of the University of Debrecen on October 5, 2016. In his inauguration speech, fellow professor István Bitskey conjured up Professor Nyirkos’s career, in which the harmony between sports and scholarship, intellectual accomplishment and physical culture not only complemented each other but may also have served as an example for members of the academic community. The outstanding athlete and the excellent linguist did not refrain from taking an active role in the management of higher education sports, which fact has been recognized by conferring the title of perennial president of the University Athletic Club upon him. His statue could not stand at a more appropriate location than the grounds of his third home.